Enhancing Indigenous health research capacity in northern Ontario through distributed community engaged medical education at NOSM: A qualitative evaluation of the community engagement through research pilot program (Canadian Medical Education Journal, 2018)
Background: The Community Engagement Through Research (CETR) program matches Indigenous communities interested in exploring their own health research questions with NOSM learners seeking experience in health services research, supervised by faculty experienced in community-based participatory research.Methods: Qualitative research was conducted using key informant interviews to examine outcomes of the matching of medical students with Indigenous distributed medical education (DME) communities in NOSM’s distributed curriculum, in particular improvements for capacity for Indigenous health research in Northern Ontario.Results: Interviews showed that community-centred research was appreciated by community, students and faculty and the social accountability aspect was acknowledged.  Students and community members found meaning in the immediate applicability of the research to real community problems and felt inspired by it. The challenges that were identified were mainly related to time and resource constraints, including providing sufficient research training for learners, and the time period required for research ethics board approvals.  Conclusions: The program successfully brought together communities interested in conducting their own health research, with medical students interested in learning about and conducting health research with Indigenous communities. It is therefore an example of successful community based participatory research supporting the social accountability mandate. Challenges are mainly administrative in nature. The program has the potential to be scalable and financially sustainable.